2023
DOI: 10.1002/tpg2.20335
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of grain amino acid composition in a UK soft wheat mapping population

Abstract: Wheat (Triticum aestivum L.) is a major source of nutrients for populations across the globe, but the amino acid composition of wheat grain does not provide optimal nutrition. The nutritional value of wheat grain is limited by low concentrations of lysine (the most limiting essential amino acid) and high concentrations of free asparagine (precursor to the processing contaminant acrylamide). There are currently few available solutions for asparagine reduction and lysine biofortification through breeding. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…A QTL for free asparagine content in grain was identified on chromosome 4B, located approximately 60 Mbp away from a QTL reported by Peng et al [59], the first time that two studies had identified QTL that might overlap. However, this QTL was also affected by environmental factors, accounting for only 2.6% of the variance in a 2017-2018 field trial of the population, but 14.8% of the variance in a 2018-2019 field trial when free asparagine concentrations were higher [61]. Even so, the Robigus allele was associated with higher free asparagine concentrations in both years.…”
Section: Identifying Quantitative Trait Loci (Qtl) That Control Free ...mentioning
confidence: 93%
See 2 more Smart Citations
“…A QTL for free asparagine content in grain was identified on chromosome 4B, located approximately 60 Mbp away from a QTL reported by Peng et al [59], the first time that two studies had identified QTL that might overlap. However, this QTL was also affected by environmental factors, accounting for only 2.6% of the variance in a 2017-2018 field trial of the population, but 14.8% of the variance in a 2018-2019 field trial when free asparagine concentrations were higher [61]. Even so, the Robigus allele was associated with higher free asparagine concentrations in both years.…”
Section: Identifying Quantitative Trait Loci (Qtl) That Control Free ...mentioning
confidence: 93%
“…Foods 2023, 12, x FOR PEER REVIEW 14 of 26 concentrations were higher [61]. Even so, the Robigus allele was associated with higher free asparagine concentrations in both years.…”
Section: Identifying Quantitative Trait Loci (Qtl) That Control Free ...mentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, asparaginase can be added to inhibit acrylamide formation [10]. Another approach is plant breeding to reduce the asparagine content already in the raw material [16], combined with the genetic control of the grain amino acid composition [17]. Furthermore, in agricultural practice, a sulfur deficiency in the soil should be avoided, as it leads to increased asparagine levels in the grain [18].…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of essential amino acid such as lysine and limiting the high concentrations of free asparagine to prevent acrylamide during bread formation enhance the nutritional value of wheat grain. The article by Oddy et al (2023) used this approach for understanding genetic control of grain amino acid composition in a UK soft wheat mapping population with major emphasis on lowering free asparagine and higher lysine content. This article used the multivariate analysis showing these traits largely independent of one another, with the largest effect on amino acids being from the environment.…”
mentioning
confidence: 99%